2007
DOI: 10.1080/08927020601001929
|View full text |Cite
|
Sign up to set email alerts
|

Computations of production yields for Ba@C74 and Yb@C74

Abstract: The paper reports computations for two C 74 -based endohedrals-Ba@C 74 and Yb@C 74 . A set of six C 74 cages is considered, namely one cage with isolated pentagons, three isomers with a pentagon -pentagon junction, two structures with one pentagon -pentagon pair and one heptagon. However, the endohedral based on the cage with isolated pentagons is the most important species in both systems. Special interest is paid to the Gibbs energy-based evaluations of the production abundances for different metallofulleren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In addition to the composition of isomeric mixtures, thermodynamic analysis can address the question of the relative yield of EMFs with different metals. Slanina et al reported such an analysis for various monometallofullernes, and recently also for Sc 2 S@C 82 /Y 2 S@C 82 . These studies revealed that the relative yields of EMFs with different metal atoms can be rationalized employing saturated vapor pressures of metals and their ionization potentials.…”
Section: Theoretical Studies Of Electronic and Molecular Structure Of...mentioning
confidence: 95%
“…In addition to the composition of isomeric mixtures, thermodynamic analysis can address the question of the relative yield of EMFs with different metals. Slanina et al reported such an analysis for various monometallofullernes, and recently also for Sc 2 S@C 82 /Y 2 S@C 82 . These studies revealed that the relative yields of EMFs with different metal atoms can be rationalized employing saturated vapor pressures of metals and their ionization potentials.…”
Section: Theoretical Studies Of Electronic and Molecular Structure Of...mentioning
confidence: 95%
“…As important members of the EMFs family, the mono-EMFs M@ D 3 h (14246)-C 74 (M = Be, Mg, ,, Ca, , Sr, ,,,, Ba, ,,,, La, Pr, Sm, , Eu, , Yb, ,,, U) have been extensively investigated. The early combined single-crystal XRD and theoretical studies on Ba@ D 3 h (14246)-C 74 elucidated that the Ba atom is off-centered and toward the [6,6] double bond on one C 2 axis of cage, and the similar on-axis position was reported for most of above metals.…”
Section: Introductionmentioning
confidence: 99%
“…For those fullerenes violating the isolated pentagon rule (IPR), 13 the metal usually resides nearby the pentagon adjacencies (PAs) to release the local cage strain by charge transfer and coordination interactions. 14,15 As important members of the EMFs family, the mono-EMFs M@D 3h (14246)-C 74 (M = Be, 16−18 Mg, 16,18,19 Ca, 16,18−26 Sr, 16,18,25,27,28 Ba, 16,18,25,27,29−32 La, 33−37 Pr, 38 Sm, 39,40 Eu, 41,42 Yb, 22,32,43,44 U 45 ) have been extensively investigated. The early combined single-crystal XRD and theoretical studies on Ba@ D 3h (14246)-C 74 elucidated that the Ba atom is off-centered and toward the [6,6] double bond on one C 2 axis of cage, 29 and the similar on-axis position was reported for most of above metals.…”
Section: Introductionmentioning
confidence: 99%